Analisis Longshore Current dan Longshore Sediment Transport pada Pantai Aeng, Galesong Utara, Kabupaten Takalar: Analysis of Longshore Current and Longshore Sediment Transport at Aeng Beach, North Galesong, Takalar Regency (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Located in the coastal region of Takalar Regency, Aeng Beach has possibilities for tourism, industrial, fishing, and seaweed industries. It shares a straight border with Makassar City. But practically all coastal regions have the issue of abrasion along the Takalar Regency's shore as a result of coastal currents. Investigating the direction and speed of longshore currents and their impact on the movement of silt down the shore is the goal of this study. Based on ten years of wind data from BMKG Region IV Makassar City, wave data analysis employs a wave forecasting technique. Empirical equations are used to calculate longshore current speed and longshore sediment transport. Based on the analysis, it can be observed that the breaking wave depth (db) varies between 2.1 and 2.5 meters, while the breaking wave height (Hb) ranges from 1.64 to 2.00 meters. The longshore current direction of the coast is east to west, and the speed ranges from 4.13 to 4.55 m/sec. According to the direction of the dominant incoming waves, the longshore sediment transport ranges from 13,159.93 – 19,674.25 m3/day or 4,803,373 – 7,181,101 m3/year from west to east. This indicates that fine sand to coarse sand dominates the sediment in the Aeng Beach area. Aeng Village Beach's abrasion management can be determined using the research findings as reference data. One of the structural treatments that can be implemented is the construction of permeable groin structures, which can regulate the quantity of sediment carried down the shore and preserve the stability of the coastline.